Corporate Volunteering: Relationship to Job Resources and Work Engagement - Boštjančič, Eva; Antolović, Sandra; Erčulj, Vanja (Frontiers in Psychology, 2018)
Employers are increasingly including volunteer activities in their social responsibility programs. At companies at which this is done in a planned manner, we can speak of the development of a corporate volunteering, which correlates with numerous positive psychological outcomes at both the individual and the organizational level. The aim of the study was to investigate the relationship between the corporate volunteering programs and job characteristics, connected with work engagement. In our study we were interested in identifying the role of the corporate volunteering in the evaluation of job resources and work engagement. The study included 274 employees from 15 Slovenian companies, of whom 62% participate in their organizations’ volunteer activities. They filled out the Job demands and resources questionnaire, the Utrecht Work Engagement Scale (UWES-17) and a scale for measuring the corporate volunteering climate. The results indicate that the carrying out of volunteer activities correlates with the perception of the corporate volunteering climate. Employees whose employers implement volunteering programs are more engaged and report higher levels of both autonomy and support from their co-workers and supervisors. Theoretical and practical implications are discussed.